2015
DOI: 10.7314/apjcp.2015.16.13.5365
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Formula of PSA, Age, Prostate Volume and Race Versus PSA Density and the Detection of Primary Malignant Circulating Prostate Cells in Predicting a Positive Initial Prostate Biopsy in Chilean Men with Suspicion of Prostate Cancer

Abstract: In this screening population the use of CPC detection predicted the presence of clinically significant prostate cancer better than the other parameters. The high negative predictive value would allow men CPC negative to avoid biopsy but remain in follow up. The formula PSA-AV did not add to the predictive performance using PSA density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
(22 reference statements)
0
4
1
Order By: Relevance
“…These results were in parallel with the former two studies. 18 19 However, while predicting high-grade PCa, we did not observe difference among PSA, PSAD, and PSA-AV in our study. This might attribute to PSA per tumor volume decreases with increasing tumor grade according to a recent study.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…These results were in parallel with the former two studies. 18 19 However, while predicting high-grade PCa, we did not observe difference among PSA, PSAD, and PSA-AV in our study. This might attribute to PSA per tumor volume decreases with increasing tumor grade according to a recent study.…”
Section: Discussioncontrasting
confidence: 81%
“…The predictive performance in the current study was better than that of all previous studies; thus, we recommend a PSA-AV cutoff of 400 in Chinese population. 18 19 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subgroups were set in Group 1 by considering region, PSA levels, age, prostate volume, method and tumor localization based on the results of meta-regression and clinical perspectives. Total serum PSA, prostate volume and age have been found to be clinically significant predictors of positive biopsy findings [45]. Within the subgroup of PSA level >=10 ng/ml and region of Asia, the pooled sensitivity was 0.65, 0.83 and specificity 0.82, 0.80.…”
Section: Varmentioning
confidence: 99%
“…[93] The same group compared this method of CPC detection with PSA kinetics, age-defined PSA cut-off values, and the Montreal nomogram, and reported that CPC detection was superior in predicting prostate cancer at first biopsy. [94][95][96] They also concluded that men with lowgrade small volume tumors, those complying with the criteria for active observation, were CPC negative. [97] Men with benign prostatic disease, especially prostatitis, may have PSA-positive circulating tumor cells detected but they were P504S negative.…”
Section: In the Detection Of Prostate Cancermentioning
confidence: 99%